Nontraumatic intrathoracic liver incarceration - Andrius Meskauskas, MD; Claire Goumard, MD, PhD (Radiology Case Reports)
Diaphragmatic hernias are a rare finding in adult population, especially in urgent settings. Nevertheless, the acute symptoms can be life-threatening and may require urgent surgical intervention. We report a rare case of a nontraumatic diaphragmatic hernia in a young adult with a history of laparotomy at the age of 1, suggesting a pre-existing malformation. The clinical presentation was dominated by respiratory symptoms and biological signs of hepatic ischemia, with no abdominal pain. Computed tomography demonstrated protrusion of the entire liver into the thoracic cavity. In this context, an emergency laparotomy was performed. The liver was reintroduced to the abdominal cavity, and the diaphragmatic defect repaired using a synthetic mesh, resulting in resolution of symptoms and a smooth postoperative recovery. Our case highlights the need for efficient diagnosis of the diaphragmatic hernias in adults, even without the context of trauma. A prompt and adequate repair of the defect, usually interposing a synthetic mesh, allows for complete and relatively fast recovery.